Ruta turística para el desarrollo económico del cantón Ventanas Provincia de Los Ríos - Medrano Soliz, Maylin Melania (2022)
He objective of the research is to show the need to implement a tourist route, which will boost the economy in the Ventanas canton, Los Ríos province, as well as promote tourism growth, since tourism in the canton does not have adequate development. despite having attractive strategic points. The study has a methodological framework, which describes the updated situation of the Ventanas canton, subject of study, as well as important authors in the field of tourism such as; Manuel Acerenza, Samuel García, etc., as well as the methods that were used to help develop the research, deepen through the theoretical foundation, the tourist route in the Canton Ventanas, and how it can improve the quality of life, welfare and economy of those directly and indirectly involved in the Tourism Sector, making the canton be recognized as a potential destination for rest and relaxation, in a natural and safe environment